Pneumothorax: observation - Li, Zhigang; Huang, Haidong; Li, Qiang; Zarogoulidis, Konstantinos; Kougioumtzi, Ioanna; Dryllis, Georgios; Kioumis, Ioannis; Pitsiou, Georgia; Machairiotis, Nikolaos; Katsikogiannis, Nikolaos; Papaiwannou, Antonis; Madesis, Athanasios; et al. (Journal of Thoracic Disease; Vol 6, Supplement 4 (October 10, 2014): Journal of Thoracic Disease (Pneumothorax: From Definition to Diagnosis and Treatment), 2014)
Pneumothorax based on the cause, it can be divided into two large categories; primary and secondary. The staging of pneumothorax plays a crucial role for treatment. Currently both thoracic surgeons and pulmonary physicians can handle efficiently treatment. Pulmonary physicians with the minimally medical thoracoscopy while thoracic surgeons with a more extensive intervention. Experience defines the outcome in most situations and not the method. In our current work we will present data regarding the observation of pneumothorax from a panel of experts.